Analysis of the Application of Article 21 Income Tax Accounting to Civil Servants Salaries in Port Authority Class II Office of Bitung - Prily Kurnia Pontoh; Linda AO Tanor; Aprili Bacilius (AIBPM Publisher, 2020)
This study aims to determine how the Application of Article 21 Income Tax Accounting to civil servant salaries in the Port Authority Office Class II of Bitung. This study used descriptive research method. The data sources were primary data and secondary data. The data were collected through observation, interviews, and documentation. The data were analyzed by collecting, deciphering, calculating, and comparing the existing data by means of an analysis to draw conclusions on Article 21 Income Tax (PPh) Calculation, Accounting Records for civil servants salaries, Article 21 Income Tax (PPh) Remittance, and Article 21 Income Tax (PPh) Statements at the Port Authority Office Class II of Bitung. The study findings indicate that the Article 21 Income Tax Calculation, Remittance and Statements in the Port Authority Office Class II of Bitung is non-compliant with the Calculation, Remittance and Statements of Article 21 Income Tax as stated by Law No. 36/2008.